2013
DOI: 10.2109/jcersj2.121.123
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitized solar cells using purified squid ink nanoparticles coated on TiO<sub>2</sub> nanotubes/nanoparticles

Abstract: Purified squid ink was used as a natural dye in TiO 2 nanocomposite films for the fabrication of dye-sensitized solar cells (DSSCs). The squid ink extract was purified by the reaction over a proteolytic enzyme and coated onto composites of TiO 2 nanotubes/ nanoparticles. The resulting cells were compared with reference DSSCs in which N719 was used as a standard dye. Analysis revealed that the sub-500-nm eumelanine-based spherical nanoparticles were well adsorbed on the surface of the TiO 2 nanotubes/ nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
0
17
0
8
Order By: Relevance
“…Purified natural melanin from squid ink and mussel-inspired synthetic polydopamine have been used as dyes in dye-sensitized solar cells. [103,116] Polydopamine/TiO 2 nanocomposites and plasmonic structures fabricated exploiting the reducing properties of polydopamine have been used for photocatalytic applications. [117][118][119] The biocompatibility and optical properties featured by TiO 2 have been used for self-cleaning, self-sterilization, and photolithography purposes [120,121] and also in fields such as cosmetics, where TiO 2 has been used as filler and UV-filter.…”
Section: Melanin/metal Oxides Interfaces: Adhesion Biocompatibilitymentioning
confidence: 99%
“…Purified natural melanin from squid ink and mussel-inspired synthetic polydopamine have been used as dyes in dye-sensitized solar cells. [103,116] Polydopamine/TiO 2 nanocomposites and plasmonic structures fabricated exploiting the reducing properties of polydopamine have been used for photocatalytic applications. [117][118][119] The biocompatibility and optical properties featured by TiO 2 have been used for self-cleaning, self-sterilization, and photolithography purposes [120,121] and also in fields such as cosmetics, where TiO 2 has been used as filler and UV-filter.…”
Section: Melanin/metal Oxides Interfaces: Adhesion Biocompatibilitymentioning
confidence: 99%
“…It was reported that the size diameter of spherical particles forming natural melanin varies in the range of 100 -200 nm [21,22,23]. Watt et al as well as Bothma found that the diameters of sepia melanin granules which are roughly spherical were 100 nm upwards [24,25]. The diameter of the aggregated spherical granules constituting sepia melanin was reported to be about 150 nm [26].…”
Section: Sem Micrographsmentioning
confidence: 99%
“…23 This leads to that only a fraction of anchored melanin has properly positioned energy levels allowing for transfer of electrons to TiO 2 and holes to the electrolyte. The inability to reproduce the results of Lee et al, 11 seems to indicate that melanin may not be reliable for functioning as the photosensitizer of DSSC. FIG.…”
Section: Resultsmentioning
confidence: 89%
“…Lee et al has reported the use of Sepia melanin as the photosensitizer in DSSC. 11 With melanin nanoparticles extracted from squid ink with particle sizes of hundreds of nanometers and an immersion process, a DSSC efficiency of 0.72% was attained. Previously, we have reported the production of melanin nanoparticles with substantially smaller particle size through photofragmentation or magnetic stir of suspended melanin powder, 12 so the MNPs produced this way were adopted for this experiment.…”
Section: -2mentioning
confidence: 99%